IL‐17 and TNF‐α co‐operation contributes to the proinflammatory response of hepatic stellate cells. (6th June 2019) - Beringer, A.; Miossec, P.
Summary: Hepatic stellate cells (HSCs) have a central role in liver inflammation and fibrosis by producing inflammatory and fibrotic mediators. Their activation is regulated through direct cell–cell interactions, but also through systemic and local effects of soluble factors such as cytokines. The effects of the proinflammatory cytokines interleukin (IL)‐17 and tumor necrosis factor (TNF)‐α and cell interactions with hepatocytes on HSC activation were assessed. Human HSC and HepaRG cells were exposed to IL‐17 and/or TNF‐α. IL‐17 and TNF‐α contribution from immune cells was determined in a co‐culture model with phytohemagglutinin (PHA)‐activated peripheral blood mononuclear cells (PBMC), HSC and/or hepatocytes. IL‐17 enhanced TNF‐α effects on the induction of IL‐6, IL‐1β, and the chemokine IL‐8, chemokine (C‐C motif) ligand 20 (CCL20) and monocyte chemoattractant protein‐1 (MCP‐1) expression/secretion in isolated HSC cultures. HSC–hepatocyte interactions did not enhance IL‐6, IL‐8 and CCL20 production compared to hepatocyte alone. However, HSC–hepatocyte interactions increased C‐reactive protein expression. IL‐17 and/or TNF‐α had no direct profibrotic effects on collagen 1 α1, tissue inhibitor of matrix metalloproteinase (TIMP) and matrix metalloproteinase (MMP) 2 gene expression, whereas mRNA levels of MMP3, an enzyme involved in matrix destruction, were up‐regulated in HSCs. The use of specific inhibitors of IL‐17 and TNF‐α indicated their contribution to the strong increase of IL‐6 and IL‐8 production induced by PBMC, HSC and/or hepatocyte interactions. As chronic liver inflammation leads to liver fibrosis, IL‐17 and/or TNF‐α neutralization can be of interest to control liver inflammation and therefore its effects on fibrosis. Abstract : IL‐17 amplifies the effects of TNF‐α on the production of pro‐inflammatory cytokines and chemokines by hepatic stellate cell. Peripheral blood mononuclear cell (PBMC), hepatocyte and/or hepatic stellate cell interactions further increases the secretion of IL‐6, IL‐8 and CCL20. The use of inhibitors of IL‐17 and TNF‐α show their contribution to such increased production of inflammatory cytokines and chemokines mediated by these cell interactions.